If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + -4) + -4 = 2y + 6.9 Reorder the terms: 3(-4 + y) + -4 = 2y + 6.9 (-4 * 3 + y * 3) + -4 = 2y + 6.9 (-12 + 3y) + -4 = 2y + 6.9 Reorder the terms: -12 + -4 + 3y = 2y + 6.9 Combine like terms: -12 + -4 = -16 -16 + 3y = 2y + 6.9 Reorder the terms: -16 + 3y = 6.9 + 2y Solving -16 + 3y = 6.9 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -16 + 3y + -2y = 6.9 + 2y + -2y Combine like terms: 3y + -2y = 1y -16 + 1y = 6.9 + 2y + -2y Combine like terms: 2y + -2y = 0 -16 + 1y = 6.9 + 0 -16 + 1y = 6.9 Add '16' to each side of the equation. -16 + 16 + 1y = 6.9 + 16 Combine like terms: -16 + 16 = 0 0 + 1y = 6.9 + 16 1y = 6.9 + 16 Combine like terms: 6.9 + 16 = 22.9 1y = 22.9 Divide each side by '1'. y = 22.9 Simplifying y = 22.9
| (-.8)(1/5)=x | | 8y=11y+3 | | w/11=3 | | 6+2(8f-2)=4(1+f) | | 6.2x-5+x-1.5=0 | | p=180*(33.333/100) | | (-4)-(-.8)=x | | (x^2+6x-4)+(-x^2-6x+4)= | | 91+(-11)= | | 5y^2+y+1y=4 | | 3/x=5/2x | | 8z+33=3(3z+11)-z | | 89=x+13(7) | | 12x^2-(121/12)=0 | | -5(x-3)=10 | | -3(2x+2)=6x-8 | | 69=3(4x-1) | | 4x-1+2x-1=5y | | -5x-19=10 | | 15x+25y=120 | | 1y=3x-3 | | 915=10a-7 | | 5(3)-7=2(3+1) | | 94+27t=715 | | 5x-4(x+2)=29 | | =-4h+5j-4j+7h | | 5(x-3)=14 | | (2x)/7=2x^2 | | 5(2x-4)+7=12+3(2x+1) | | 816=24(v+12) | | 3)x-y)/5(2x/3y) | | -7(1+5x)=7(x+5) |